Government procurement and access to credit: Firm dynamics and aggregate implications - Julian Di Giovanni; Manuel García-Santana; Priit Jeenas; Enrique Moral-Benito; Josep Pijoan-Mas (Federal Reserve Bank of New York, 2022)
We provide a framework to study how different allocation systems of public procurement contracts affect firm dynamics and long-run macroeconomic outcomes. We start by using a newly created panel data set of administrative data that merges Spanish credit register loan data, quasi-census firm-level data, and public procurement projects to study firm selection into procurement and the effects of procurement on credit growth and firm growth. We show evidence consistent with the hypotheses that there is selection of large firms into procurement, that procurement contracts provide useful collateral for firms more so than sales to the private sector and that procurement contracts facilitate firm growth beyond the contract duration. We next build a model of firm dynamics with both asset-based and earnings-based borrowing constraints and a government that buys goods and services from private sector firms. We use the calibrated model to quantify the long-run macroeconomic consequences of alternative procurement allocation systems. We find that granting procurement contracts to small firms, either by directly targeting them or by slicing large contracts into smaller ones, helps these firms grow and overcome financial constraints in the long run. However, we also find that reducing the average size of contracts or making it less likely for large firms to access them removes saving incentives for large firms, whose negative effects on capital accumulation can overcome the expansionary consequences for small firms and hence generate a drop in aggregate output.
Keywords: E22; E23; E62; G32; 330; government procurement; financial frictions; capital accumulation; aggregate productivity